Do natural disasters affect household saving? Evidence from the August 2002 flood in Germany - Michael Berlemann; Erik Haustein; Max Friedrich Steinhardt; Jascha Tutt (Freie Universität Berlin, School of Business & Economics, 2024)
Recently, there is a growing interest in understanding how individuals adapt to changing climate conditions and climate-induced extreme weather events, An underexplored question is whether and how climate-related natural hazards affect household saving behavior, For this purpose, we exploit a natural experiment stemming from the European Flood of August 2002, Combining micro data with geo-coded flood maps allows us to analyze the causal impact of flood exposure on household savings within a differences-in-differences setting, We find that flood exposure depresses household saving behavior in the medium run, The most likely explanation is moral hazard induced by massive government support for affected households.
urn:nbn:de:kobv:188-refubium-45595-4
Keywords: D14; H84; Q54; 330; Natural disasters; flood; saving behavior; natural experiment